Improving Rural Access to Opioid Treatment Programs. Issue 2 (2018) - Johnson, Quentin; Mund, Brian; Joudrey, Paul J.
Abstract : This article explores challenges to accessing opioid treatment programs in rural areas, and offers solutions that would ease these problems.